Deception by topic choice: How discussion can mislead without falsehood. (10th August 2021) - Cross, Ben
Abstract: This article explains and defends a novel idea about how people can be misled by a discussion topic, even if the discussion itself does not explicitly involve the making of false claims. The crucial aspect of this idea is that people are liable to infer, from the fact that a particular topic is being discussed, that this topic is important. As a result, they may then be led to accept certain beliefs about the state of the world they consider necessary for the topic's importance. What the article calls "importance misrepresentation" occurs when these beliefs about the state of the world are false or otherwise mistaken. The article explores different ways in which importance misrepresentation can occur, and it uses this idea to help clarify and strengthen some well‐known criticisms of the topic choices of academic philosophers.